Modifications in Adenoviral vectors to enhance its tropism: a literature review - Erly Sintya; Ni Luh Putu Harta Wedari; Ni Nyoman Sri Budayanti; Ni Luh Made Mirah Rahayu (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
Viruses’ high rate of cellular entry raises the possibility that they could be utilized as vectors to introduce new functional copies of a gene into a cell. This review aims to explore modifications in Adenoviral vectors to enhance its tropism. It is feasible to exploit the infection pathway to achieve a therapeutic objective without the following expression of viral genes, which, if expressed, would cause disease and damage. It has been demonstrated that this is achievable. This is performed by swapping a therapeutic gene with an existing harmful gene in the genome of the virus. Due to its unique features, adenovirus, commonly known as Ad, is an intriguing possibility for use as a viral vector in gene therapy. Despite this, therapeutic applications of ad vectors are limited due to their immunogenicity and broad native tropism. Several distinct forms of nonimmunogenic polymers are utilized in the chemical or physical modification of ad vectors to circumvent these obstacles. In this review, many modifications, including capsid pseudotyping, serotype switching, and multiple conjugation-based techniques, are discussed in order to boost the specificity of target adenoviruses.